Pemikiran Filsafat Jürgen Habermas dalam Mengkaji Kolonisasi Dunia Kehidupan di Era Digital - Rifky Sandi Haikal; M. Ade Ilham; Mardhihah Abbas; Ilham Arifin (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study aims to analyze the relevance of Jürgen Habermas's thought in understanding the phenomenon of modern spirituality and the social dynamics of Generation Z in the digital era. Using a qualitative research method with a philosophical-analytical approach, this study examines Habermas's central concepts such as communicative action, the public sphere, the lifeworld, and discourse ethics. The results indicate that modern spirituality, which is personal and fluid, serves as a form of cultural resistance against the colonization of the lifeworld by the instrumental rationality of economic and bureaucratic systems. Meanwhile, Generation Z faces significant challenges within a digital public sphere that is often distorted by algorithms, polarization, and misinformation, which hinders the establishment of rational and deliberative communication. The study concludes that Habermas's theory provides a crucial normative framework for revitalizing healthy dialogue, constructing emancipatory digital ethics, and assisting Generation Z in restoring the depth of life's meaning amidst the pressures of the modern system.